2010
DOI: 10.1080/09064710903103917
|View full text |Cite
|
Sign up to set email alerts
|

Performance of six European plum cultivars on four plum rootstocks growing in a northern climate

Abstract: The performances of the plum rootstocks Marianna GF 8-1, Pixy, and Wangenheim, compared with St. Julien A as a standard, for the cultivars 'Avalon', 'Edda', 'Excalibur', 'Jubileum', 'Reeves', and 'Victoria' were assessed in a field trial in western Norway at 608 North. Trees were planted in spring 1999; the plant material was one-year-old whips, spaced 2.0 )4.5 m and formed with a central leader as free spindles. Tree vigour, yield, fruit size, fruit quality, and yield efficiency were evaluated for the seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
3
8
1
3
Order By: Relevance
“…The yield efficiency obtained for trees of the other cultivars assessed was 2-4 times lower than for trees of the cultivar 'Victoria' , which is consistent with the results obtained by other authors (Hjeltnes 1994;Meland, Moe 2007;Meland 2010).…”
Section: Growth and Yielding Of Treessupporting
confidence: 91%
See 2 more Smart Citations
“…The yield efficiency obtained for trees of the other cultivars assessed was 2-4 times lower than for trees of the cultivar 'Victoria' , which is consistent with the results obtained by other authors (Hjeltnes 1994;Meland, Moe 2007;Meland 2010).…”
Section: Growth and Yielding Of Treessupporting
confidence: 91%
“…Fruits of the cultivars: 'Jubileum' , 'Reeves' and ' Avalon' were also larger than those of 'Victoria' , which is consistent with results obtained by other authors (Jones 1989;Meland, Moe 2007;Meland 2010). 'Edda' produced the smallest fruits.…”
Section: Fruit Ripening Time and Fruit Qualitysupporting
confidence: 91%
See 1 more Smart Citation
“…Differences in leaf concentration of major nutrients between trees on different rootstocks are likewise attributable to the inherent capacity of the rootstock to absorb nutrients (Meland, 2010;Mestre et al, 2015Mestre et al, , 2017. In the present work, most of the nutrients were not affected by cultivar, rootstock and the interaction of both, with the exception of N, P and Mn.…”
Section: Discussionsupporting
confidence: 43%
“…Therefore, as previously reported (Milosevic and Milosevic, 2010;Rosati et al, 1996), it can be concluded that various rootstocks have different uptake ability of macronutrients. Inherent ca-pacity of the different rootstocks to major nutrient absorption and translocation is different (Meland, 2010;Mestre et al, 2015Mestre et al, , 2017. In the present work, leaf concentrations of most of the nutrients studied were not significantly affected by rootstock, with the exception of a few elements.…”
Section: Discussioncontrasting
confidence: 41%